Effort and Belief Pedagogies in a Post Primary DEIS context - Egan, Jeffrey (STER, 2024)
This article aims to highlight teacher awareness about wellbeing pedagogies that consider the PISA 2018 wellbeing metrics, related to a DEIS setting. PISA 2018 investigated growth mindset, self-efficacy and meaning in life when considering student wellbeing. The motivation for choosing this topic to research was my own lack of awareness about student wellbeing and its impact on learning. Drawing on a combination of pedagogical theories and my own lived experience in the DEIS classroom, I developed a wellbeing pedagogical framework to help anchor my reflections. This article will provide teachers and educators with information to consider how growth mindset theory, students self-efficacy and sense of purpose, embedded with an attitude of grit can contribute to positive wellbeing. Two attitudes which are linked across all these concepts are ‘belief’ and ‘effort’. Frequently, in discussion about wellbeing, as educators, we can overcompensate our awareness levels of student’s anxieties and difficulties, and sometimes can be slower to take corrective action to build up character traits in students which can help them cope with difficulties. This article is a snapshot of a broader dissertation, which examined how student wellbeing is impacted by their circumstances in life, considering a trauma informed approach and how the student-teacher relationship creates an environment of compassion to aid student wellbeing while investigating how PISA related pedagogies can enable learning.
Keywords: Growth Mindset; Self Efficacy; Meaning in Life; PISA